2004
DOI: 10.1111/j.1468-2338.2004.00311.x
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for change in public sector industrial relations: the erosion of national bargaining in further education in England and Wales

Abstract: The recent transformation of industrial relations in further education in England and Wales is examined, in particular the role of the national 'Silver Book' dispute over lecturers' conditions of service in causing the erosion of national bargaining in the sector. The experience of further education points to the limits of the strategic choice approach as a device for explaining change in public sector industrial relations and to the importance of supplementing it with a perspective that emphasises the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Our analysis (shown in Table 2) revealed that managers in the public sector were much more negative about the effects of organisational change than those in the private sector across all our measures. This is consistent with other researchers who focus specifically on the public sector (see Diefenbach, 2009;Avis, 2005;Williams, 2004). We are not against organisational change as organisations cannot be preserved in aspic or they will ossify, become less competitive and, ultimately, die.…”
Section: The Effects Of Organisational Change On Managers' Views Of Tsupporting
confidence: 70%
“…Our analysis (shown in Table 2) revealed that managers in the public sector were much more negative about the effects of organisational change than those in the private sector across all our measures. This is consistent with other researchers who focus specifically on the public sector (see Diefenbach, 2009;Avis, 2005;Williams, 2004). We are not against organisational change as organisations cannot be preserved in aspic or they will ossify, become less competitive and, ultimately, die.…”
Section: The Effects Of Organisational Change On Managers' Views Of Tsupporting
confidence: 70%
“…A detailed exposition of the differences between the established Silver Book contract and the CEF-backed contract is covered by Williams (2004, pp. 238-242).…”
Section: Data and Findingsmentioning
confidence: 99%
“…A by-product of this de-regulatory manoeuvre was a marginalisation of the teaching unions: 'I legislated for LMS and it diminished the power of the teacher unions and the LEAs' (Davies 1999). The F&HE Act had similar de-regulatory aims for the FE sector as it aimed to shelve long-standing contractual arrangements -namely the Silver Book -within colleges (Williams 2004). It signalled a determination to 'improve the productivity' of FE: in the first three years of incorporation, colleges were required to increase unit totals by 24%.…”
mentioning
confidence: 99%
“…One of the key aspects of public sector employment that has been under threat from the government and employers is the 'traditional' national bargaining system. However, it is important to recognize that this has been highly uneven between different areas of the public sector (see Duncan, 2001;Williams, 2004). It is also uneven geographically.…”
Section: New Labour and Public Sector Industrial Relationsmentioning
confidence: 99%